Effect of Tropical Fruit Juices on Surface Roughness of Tooth Coloured Restorative Materials - Siti Musfirah Binti Mustain; Aws Hashim Alkadhim; Faizah Abdul Fatah; Azlan Jaafar (NorCal Open Access Publications, 2024)
Non-Indexed Publication